Municipal Gross Domestic Product: Concept, methodology, and analysis for the city of Rio de Janeiro - Santiago, Gilda (2008)
This text was produced in response to a request from the Pereira Passos Municipal Institute of Urbanism (IPP) and is aimed at readers with little or no familiarity with the subject. The central goal is to provide them with a better understanding of the work involved in the preparation of the Gross Domestic Product (GDP) of municipalities, for the more appropriate use of this information.